Acetabular Wall Indices Help to Distinguish Acetabular Coverage in Asymptomatic Adults With Varying Morphologies. Issue 4 (April 2017) - Anderson, Lucas A.; Anderson, Mike B.; Erickson, Jill A.; Chrastil, Jesse; Peters, Christopher L.
Abstract: Background: The anterior wall index (AWI) and posterior wall index (PWI) have been proposed to quantify anterior and posterior acetabular coverage using AP pelvic radiographs. However, these indices have only been reported in symptomatic patients with apparent pathomorphologies (dysplasia, overcoverage, and retroversion) undergoing osteochondroplasty or reorientation osteotomy. Questions: (1) What are the ranges for AWI and PWI from measurements obtained on AP pelvic radiographs of asymptomatic senior athletes with well‐functioning hips? (2) Is there a difference between the AWI and PWI in asymptomatic athletes with acetabular morphology consistent with acetabular dysplasia, overcoverage, and retroversion when compared with asymptomatic hips that do not meet the radiographic definitions for those morphologies (controls)? Methods: Five hundred five athletes (998 asymptomatic native hips) were independently evaluated by two readers on AP pelvic radiographs for AWI and the PWI after excluding hips with prior surgery, inadequate radiographs, or poor function (modified Harris hip score < 80). Hips with a lateral center‐edge angle (LCEA) ≥ 20° and ≤ 38° and without acetabular retroversion, based on a positive crossover sign, were used as controls. Hips were categorized as developmental dysplasia of the hip (DDH; undercoverage) if the LCEA was < 20°. Finally, overcoverage was defined as an LCEA > 38°. The mean age of the athletes was 67 years (range, 50‐91 years) and 55% were men. Linear generalized estimating equation regression was used to compare each individual diagnosis (DDH, retroversion, overcoverage) with the controls for both AWI and PWI adjusting for age and sex. Results: The mean AWI in the study population was 0.36 (range, −0.02 to 0.91). The mean PWI was 1.13 (range, 0.12‐1.74). The mean AWI and PWI in controls (n = 740) was 0.35 (range, −0.02 to 0.91) and 1.13 (range, 0.64‐1.70), respectively. There were 25 (3%) with DDH in whom the mean AWI was 0.26 (range, 0.05‐0.5) and the mean PWI was 1.03 (range, 0.71‐1.3). There were 112 (11%) retroverted hips in whom the mean AWI was 0.42 (range, 0.1‐0.89) and PWI was 1.02 (range, 0.61‐1.5). There were 121 (12%) overcovered hips in whom the mean AWI was 0.43 (range, −0.18 to 0.85) and PWI was 1.22 (0.12‐1.74). The AWI in the control hips was no different than that of DDH hips (β −0.06; 95% confidence interval [CI], −0.12 to 0.002; p = 0.059) but was found to be lower than retroverted hips (β 0.08; 95% CI, 0.04‐0.11; p < 0.001) and overcovered hips (β 0.05; 95% CI, 0.03‐0.08; p < 0.001). The PWI in control hips was greater than that of DDH hips (β −0.08; 95% CI, −0.14 to −0.02; p = 0.013) and retroverted hips (β −0.07; 95% CI, −0.11 to −0.04; p < 0.001) but was less than overcovered hips (β 0.07; 95% CI, 0.04‐0.10; p < 0.001). Conclusions: The measurements of AWI and PWI in well‐functioning, asymptomatic hips may be useful in assessing anterior and posterior acetabular coverage because it was able to distinguish between different types of known pathologic morphology. Despite evidence of these morphologic variances, these senior athletes continued to function at a high level. Thus, the identification of morphologic variance was not consistent with signs of pathology, which further supports that early screening of morphology may not predict the development of symptomatic pathology. Future work should focus on comparing these indices for morphologic variance in both symptomatic and asymptomatic hips to determine whether these measurements can be used in identifying problematic hips and as reference ranges for surgical correction. Level of Evidence: Level III, diagnostic study.